A case of sudden hearing loss during treatment with decitabine for chronic myelomonocytic leukemia - Kim, Hee-Jun; Park, Eun-Kyung; Moon, In-Seok (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Chronic myelomonocytic leukemia (CMML) was initially classified in the category of myelodysplastic syndrome (MDS), but it is now categorized by the 2001 World Health Organization (WHO) classification in a separate nosological group of MDS. Unlike chronic myeloid leukemia (CML), the bone marrow morphology in CMML demonstrates prominent dysplastic changes in at least two of the three myeloid lineages. A 73-year-old male patient was brought to division of hematology for evaluation of leukocytosis. He was diagnosed with CMML and treated with decitabine. The hearing impairment had arisen during the third cycle of decitabine. To our knowledge, this is the first case that idiopathic sudden hearing loss (SHL) occured in CMML patients during treatment with decitabine.